Allopurinol use associated with increased risk of acute myocardial infarction in older people in a case–control study - Kuan-Fu Liao; Cheng-Li Lin; Shih-Wei Lai (Tzu Chi Medical Journal)
Objective: There is controversy about the association between the allopurinol use and the risk of acute myocardial infarction. The aim of the study was to examine the association between allopurinol use and acute myocardial infarction in older people in Taiwan. Materials and Methods: We used the 2000–2013 database of the Taiwan National Health Insurance Program to conduct a case–control study. Cases were assigned as subjects aged 65 years and older with the first incident acute myocardial infarction. Matched controls were assigned as subjects aged 65 years and older without any type of coronary artery disease. Ever use of allopurinol was defined as subjects who had at least a prescription of allopurinol before the diagnosis date of first incident acute myocardial infarction. The odds ratio (OR) and the 95% confidence interval (CI) for acute myocardial infarction associated with allopurinol use were estimated by the multivariable logistic regression model. Results: There were 4701 cases with the first incident acute myocardial infarction and 9369 matched controls. The adjusted OR of acute myocardial infarction was 2.2 (95% CI 1.7– 2.7) for subjects with ever use of allopurinol, compared with never use. The adjusted ORs of acute myocardial infarction were 2.0 (95% CI 1.5–2.6) for subjects with average daily dosage of allopurinol <200 mg and 2.5 (95% CI 1.6–4.0) for subjects with average daily dosage of allopurinol ≥200 mg. Conclusion: Allopurinol use is associated with increased odds of acute myocardial infarction in older people, which is dosage dependent.